PENGARUH STRATEGI PEMBELAJARAN ECIRR TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA - Lia Kurniawati; Umi Masruro; Afidah Afidah (ALGORITMA: Journal of Mathematics Education, 2020)
The purpose of this research was analyze students’ mathematical critical thinking skills using ECIRR strategy. The Reseacrh was conducted at one of Islamic schools in the city of Tangerang Selatan.. Method of the research used quasi experiment method with posttest-only control group design. The samples are 53 students, they are 26 students in experimental group and 27 student in control group that chosen by cluster sampling technique. The collecting data of students’ mathematical critical thinking skills used by test instrument. The result of this research shown that students’ mathematical critical thinking skills who are taught by ECIRR strategy is higher than students who are taught by conventional strategy. Means of mathematical critical thinking skills of students’ who are taught by ECIRR strategy had skill of analyze the argument amounting to 84.62, draw a conclusion amounting to 68.27, identify assumptions amounting to 73.08, and decide an action amounting to 40,38. As for students’ who are taught by conventional strategy had skill of analyze the argument amounting to 85.19, draw a conclusion amounting to 44.91, identify assumptions amounting to 24.07, and decide an action amounting to 23.15. The conclusion of this research that ECIRR strategy have a significant effect on students’ mathematical critical thinking skills.